Productive performance, egg quality and bone characteristics of quails fed with meal and canola oil - Moraes, Priscila de Oliveira; Gopinger, Edenilse; Bavaresco, Caroline; Catalan, Aiane Aparecida da Silva; Dias, Renata Cedres; Xavier, Eduardo Gonçalves (Acta Scientiarum. Animal Sciences, 2017)
This study evaluated the effect of canola meal and oil in quail diet on productive performance, egg quality and bone characteristics. Quails (n = 84) with 150-days-of-age and average weight of 234±17 g were used in this experiment that lasted 84 days. The experiment consisted of a completely randomized design with 4 treatments, 7 replications with 3 birds each. Four diets were formulated: SM+SO - control diet with soybean meal and oil; MC+SO - 25% replacement of soybean meal with canola meal; MC+CO - 25% replacement of soybean meal with canola meal and complete replacement of canola oil with soybean oil; SM+OC - control diet with soybean meal and canola oil. Productive performance, internal and external egg quality and bone characteristics were evaluated. The diet with canola meal and oil (MC+CO) decreased (p <0.05) feed conversion. Albumen height was lower (p < 0.05) for treatments with canola meal and oil (MC+CO). Regardless of the oil used, the dietary canola meal (MC+SO and MC+CO) reduced the weight and length of tibia (p < 0.05), but increased its ash content (p < 0.05). The mixture of canola oil and meal decreases feed conversion, and negatively affects internal egg quality and bone characteristics of quails.